Breast Necrosis after Chemotherapy for Recurrent Ovarian Cancer: Report of a Case and Review of the Literature. Issue 4 (25th April 2015) - Matloob, Reza; Alikhasi, Afsaneh; Shirkhoda, Mohammad; Najafi, Massoome
Abstract Breast necrosis is a rare event due to abundant blood supply of the breast. We present an unusual case of partial breast necrosis after chemotherapy for recurrent ovarian cancer. Necrotic tissue sloughed with conservative management and the wound was repaired surgically. We believe that this is the first case report of breast necrosis as a systemic complication of chemotherapy.